Chitosan-Based In-Situ Gels for Topical Drug Delivery: A Review of Mechanisms, Applications, and Future Prospects - Fikri Alatas; Wahyu Ammarullah (Universitas Wahid Hasyim Semarang, 2026)
Topical drug delivery systems are rapidly evolving to enhance therapeutic efficacy and patient compliance. Among these, in-situ gelling systems that transition from a sol to a gel state in response to physiological stimuli have emerged as a highly promising platform. This review provides a comprehensive analysis of chitosan, a natural polysaccharide, as a cornerstone polymer for the development of advanced in-situ gels. This paper, based on a systematic literature review of 63 articles published between 2015 and 2025, explores the formulation, characterization, and application of these intelligent delivery systems. Key findings highlight chitosan's exceptional properties, including biocompatibility, biodegradability, and mucoadhesion, which are crucial for effective topical therapy. The review details the primary gelation mechanisms, such as pH, temperature, and ion sensitivity that enable controlled, localized drug release. Furthermore, it summarizes extensive preclinical evidence demonstrating the versatility of chitosan-based gels in various applications, including ocular, nasal, wound healing, and even nose-to-brain drug delivery, where they significantly improve bioavailability and prolong residence time. While challenges like poor solubility and weak mechanical strength persist, innovative solutions involving polymer blending and chemical modification are effectively expanding their functional capabilities. This review concludes that chitosan-based in-situ gels represent a sophisticated and adaptable platform poised to advance next-generation, non-invasive therapeutics.